2010
DOI: 10.1242/dev.051789
|View full text |Cite
|
Sign up to set email alerts
|

Preaxial polydactyly: interactions among ETV, TWIST1 and HAND2 control anterior-posterior patterning of the limb

Abstract: SUMMARYPreaxial polydactyly (PPD) is a common limb-associated birth defect characterized by extra digit(s) in the anterior autopod. It often results from ectopic sonic hedgehog (Shh) expression in the anterior limb bud. Although several transcription factors are known to restrict Shh expression to the posterior limb bud, how they function together remains unclear. Here we provide evidence from mouse conditional knockout limb buds that the bHLH family transcription factor gene Twist1 is required to inhibit Shh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 54 publications
(95 reference statements)
3
66
0
Order By: Relevance
“…It should be noticed that, in the Twist1 null mutant, Etv4 and Etv5 are also up-regulated in the anterior limb bud mesenchyme, which does not preclude Shh derepression anteriorly. Indeed, it has been recently demonstrated that Etv and Twist1 proteins form a complex that is required to repress Shh anteriorly (Zhang et al, 2010). The similarity between these and our results may suggest a similar mechanism for anterior repression of Shh by Msx.…”
Section: Control Of Shh Expressionsupporting
confidence: 88%
See 1 more Smart Citation
“…It should be noticed that, in the Twist1 null mutant, Etv4 and Etv5 are also up-regulated in the anterior limb bud mesenchyme, which does not preclude Shh derepression anteriorly. Indeed, it has been recently demonstrated that Etv and Twist1 proteins form a complex that is required to repress Shh anteriorly (Zhang et al, 2010). The similarity between these and our results may suggest a similar mechanism for anterior repression of Shh by Msx.…”
Section: Control Of Shh Expressionsupporting
confidence: 88%
“…It should be noted that the Prx1-Cre transgene activity takes place progressively in both fore-and hindlimbs (Logan et al, 2002), and that, at the earliest stages of limb outgrowth, some Msx activity is likely to remain in the mesenchyme of our conditional mutant. A recent study (Zhang et al, 2010) has shown that for Twist1, a gene specifically expressed in the limb bud mesoderm, the Prx1-Cre-induced null mutation leads to a less dramatic phenotype than the constitutive null mutation. In particular, AER development is complete in the conditional null mutant and impaired in the constitutive one.…”
Section: Conditional Mutantmentioning
confidence: 99%
“…Sustained expression of Twist1 in cartilage led to a growth phenotype, characterized by shortening of the limbs and reduced body mass. Various Twist1 loss of function studies have also reported growth abnormalities and limb dismorphogenesis (Firulli et al, 2005, Firulli et al, 2007, Krawchuk et al, 2010, Zhang et al, 2010, thus demonstrating that in addition to its established function during intramembranous bone formation, Twist1 also plays a role in endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their histological analyses of the developing ribs and limbs in a1(II) Collagen-Cre; Twist1 fx embryos (E13.5 and E16.5), showed no obvious phenotype attributable to Twist1 gene inactivation in chondrocytes (Hinoi et al, 2006). However, conditional Twist1 abrogation from the limb mesenchyme by crossing Twist1 fx mice with mice containing the Prx1-Cre transgene, which activates Cre expression in prechondrocytes, resulted in forelimb patterning defects, hypoplastic scapula and clavicle, tibial aplasia, and preaxial polydactyly characterized by severe disorganization of cartilage elements (Krawchuk et al, 2010, Zhang et al, 2010. We speculated that the temporal requirement for Twist1 during postnatal chondrocyte formation may provide novel insight into stage-and dose-dependent roles of Twist1 during cartilage maturation and maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation